2013
DOI: 10.5194/acp-13-7115-2013
|View full text |Cite
|
Sign up to set email alerts
|

Towards better error statistics for atmospheric inversions of methane surface fluxes

Abstract: We adapt general statistical methods to estimate the optimal error covariance matrices in a regional inversion system inferring methane surface emissions from atmospheric concentrations. Using a minimal set of physical hypotheses on the patterns of errors, we compute a guess of the error statistics that is optimal in regard to objective statistical criteria for the specific inversion system. With this very general approach applied to a real-data case, we recover sources of errors in the observations and in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 54 publications
(66 reference statements)
1
77
0
Order By: Relevance
“…We then sample the observations during the afternoon when the PBL is higher than 500 m as suggested by prior studies (e.g. Berchet et al, 2013b) and we pick the observed and simulated mixing ratios at the time when the observations are minimum.…”
Section: Observation Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…We then sample the observations during the afternoon when the PBL is higher than 500 m as suggested by prior studies (e.g. Berchet et al, 2013b) and we pick the observed and simulated mixing ratios at the time when the observations are minimum.…”
Section: Observation Samplingmentioning
confidence: 99%
“…Recent studies inquired into objectified ways of specifying these matrices (e.g. Michalak and Kitanidis, 2005;Winiarek et al, 2012;Berchet et al, 2013b). The approach in these papers was to find optimal uncertainty matrices R and B along an objective statistical criterion: the maximum likelihood.…”
Section: Motivations Towards Marginalizingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the impact of assumptions about the statistical representation of prior errors and model-data-mismatch errors can be examined by performing multiple inversions, as can the impact of approaches aimed at optimizing these error statistics (e.g., Bousquet et al, 2011;Cressot et al, 2014;Wu et al, 2013;Ganesan et al, 2014;Berchet et al, 2013). Sensitivity tests may also be run on other statistical parameters such as the assumed correlation length of fluxes (Corazza et al, 2011).…”
Section: Statistical and Computational Frameworkmentioning
confidence: 99%
“…In the simplest case, spatially aggregated posterior fluxes can be assessed based on expert knowledge of the system. For example, methane emissions in regions dominated by natural gas extraction, urbanization, wetlands, or cattle feedlots are expected to substantially outweigh soil methane uptake, and negative estimated emissions in such regions would point to errors in the inversion (e.g., Berchet et al, 2013). Similarly, global decadal atmospheric growth rates and latitudinal gradients of greenhouse gases are well constrained by long-term baseline observations (e.g., Conway et al, 1994), and posterior flux estimates can be evaluated against such large-scale constraints (e.g., Cressot et al, 2014).…”
Section: Evaluation At Aggregated Scales Against Large-scale Scientifmentioning
confidence: 99%